Metal deposition of copper and lead bullets in moose harvested in Fennoscandia - Sigbjørn Stokke; Scott Brainerd; Jon M. Arnemo (Wildlife Society Bulletin)
ABSTRACT Fragments from bullets used for moose (Alces alces) hunting contaminate meat, gut piles, and offal and expose humans and scavengers to lead and copper. We sampled bullets (n = 1,655) retrieved from harvested moose in Fennoscandia (Finland, Sweden, and Norway) to measure loss of lead and copper. Concordant questionnaires (n = 5,255) supplied ballistic information to complete this task. Hunters preferred lead‐based bullets (90%) to copper bullets (10%). Three caliber classes were preferred: 7.62 mm (69%), 9.3 mm (12%), and 6.5 mm (12%). Bullets passed completely through calves (76%) more frequently compared to yearlings (63%) or adults (47%). Metal deposition per bullet type (bonded lead core, lead core, and copper) did not vary among moose age classes (calves, yearlings, and adults). Average metal loss per bullet type was 3.0 g, 2.6 g, and 0.5 g for lead‐core, bonded lead‐core, and copper bullets, respectively. This corresponded to 18–26, 10–25, and 0–15% metal loss for lead‐core, bonded lead‐core, and copper bullets, respectively. Based on the harvest of 166,000 moose in Fennoscandia during the 2013/2014 hunting season, we estimated that lead‐based bullets deposited 690 kg of lead in moose carcasses, compared with 21 kg of copper from copper bullets. Bone impact increased, whereas longer shooting distances decreased, lead loss from lead‐based bullets. These factors did not influence loss of copper from copper bullets. In conclusion, a significant amount of toxic lead from lead‐based bullets is deposited in the tissue of harvested moose, which may affect the health of humans and scavengers that ingest it. By switching to copper bullets, Fennoscandian hunters can eliminate a significant source of lead exposure in humans and scavengers. © 2017 The Wildlife Society.